Xylopic acid from Xylopia aethiopica (Annonaceae) inhibits morphine tolerance in rats - Priscilla Kolibea Mante; Kweku Abakah-Ewusi; Amanda Adoley Mingle; Mustapha Seidu Kpienaan; Samuel Offei-Twum; Nana Kofi Kusi-Boadum; Nana Ofori Adomako; Newman Osafo (Faculty of Pharmacy, Mahidol University, 2022)
Traditionally, Xylopia aethiopica is used to manage pain disorders such as neuralgia, colic pain, rheumatism and headache. Using animal models, this study aimed to investigate the ability of Xylopic Acid (XA), a kaurene diterpene obtained from Xylopia aethiopica, to cause tolerance when administered alone or combined with morphine. Development of withdrawal symptoms on discontinuation was also investigated. Tolerance to morphine was induced in rats through an 8-day regimen of chronic administration of morphine (10 mg/kg; twice daily). Effects of XA alone (100 mg/kg) or XA (10-100 mg/kg) on morphine tolerance and withdrawal syndrome precipitated with naloxone hydrochloride (3 mg/kg) were also assessed. XA's mechanism of action was then explored through drug-receptor binding. Chronic morphine administration in rats resulted in analgesic tolerance and morphine withdrawal syndrome. Chronic XA administration did not result in tolerance to XA's antinociceptive effect. Development of morphine withdrawal syndrome precipitated by naloxone and morphine tolerance was significantly (F(12, 60)=29.88, p<0.0001) inhibited by XA. Xylopic acid inhibited development of diarrhea, jumps and weight loss. Pretreatment with ?-2-adrenoceptor antagonist, yohimbine, 5HT3 antagonist, ondansetron and muscarinic antagonist, atropine, significantly (p=0.0042) blocked the inhibitory effect of XA on withdrawal jumps. Pretreatment with naloxone produced similar effects on withdrawal jumps as XA alone. Drug-receptor binding assays revealed a lack of significant interaction of XA on alpha-2 adrenoceptors (A, B, C) but exhibited significant DOR- selective antagonism similar to naltrindole. This study reveals that xylopic acid significantly inhibits morphine antinociceptive tolerance and withdrawal in rats. This is the first report of xylopic acid's antagonism on delta opioidergic receptors and potential as an inhibitor of chronic morphine tolerance.